2014
DOI: 10.1111/jcpt.12206
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and personalized medicine

Abstract: SUMMARYWhat is known and objective: Variation in the expression of drug-response-related genes contributes significantly to interindividual differences in drug response. DNA methylation is one of the most common epigenetic modifications that control gene expression. DNA methylation may occur in genes encoding drug metabolizing enzymes (DMEs), drug transporters and drug targets, and can thereby alter the pharmacokinetics and pharmacodynamics of drugs. In this review, we discuss recent advances in pharmacoepigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Epigenetic modifications, such as DNA methylation and histone methylation/acetylation, constitute an additional layer of gene expression regulation and affect phenotypic heterogeneity of human diseases and drug responses [ 12 , 13 ]. DNA methylation mainly occurs in the context of CG dinucleotides (CpGs) and has traditionally been associated with gene repression [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic modifications, such as DNA methylation and histone methylation/acetylation, constitute an additional layer of gene expression regulation and affect phenotypic heterogeneity of human diseases and drug responses [ 12 , 13 ]. DNA methylation mainly occurs in the context of CG dinucleotides (CpGs) and has traditionally been associated with gene repression [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic modifications have largely been implicated in cancer, among other diseases, and represent an important class of drug targets [ 26 , 27 ]. Indeed, DNA methylation has been shown to play a significant role in regulating the expression of members of the cytochrome P450 superfamily of enzymes, which is responsible for the metabolism of over 75 percent of commonly-prescribed pharmaceuticals [ 28 30 ]. While significant evidence exists in the literature for the epigenetic regulation of genes involved in the absorption, distribution, metabolism, and excretion (ADME) of drugs [ 31 ], the clinical relevance of this regulation remains to be seen.…”
Section: Pharmacogenomicsmentioning
confidence: 99%
“…Polymorphisms in the CYP2A6 --CYP2A7 gene cluster are associated with nicotine level in plasma [58]. Evidence has also shown that polymorphism at the CYP2C gene cluster can cause allele-specific DNA methylation for the genes of this cluster [69].…”
Section: Epigenetic Regulation Of Cyp Gene Expressionmentioning
confidence: 99%